2019
DOI: 10.1038/s41598-019-39879-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral contraceptive pill-exposure alone does not reduce the risk of bacterial vaginosis recurrence in a pilot randomised controlled trial

Abstract: We conducted a pilot open-label randomised controlled trial of combined (oestrogen-progesterone) oral contraceptive pill (COCP)-exposure aimed to examine its effect on BV-recurrence following first-line antibiotics compared to antibiotics alone. Ninety-five women with symptomatic BV were prescribed antibiotic therapy, randomised to COCP-exposure (intervention) or current non-hormonal contraceptive practices (control) and followed monthly for six-months or until BV-recurrence. Modified intention-to-treat method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 41 publications
2
31
1
1
Order By: Relevance
“…However, reviews of the early partner treatment trials also highlighted the significant issues that render their findings inconclusive [10,18,19]. Since the publication of these partner-treatment trials, an increasing body of epidemiological data shows women with a regular partner are more likely to experience post-treatment recurrence compared to women with no partner or a new posttreatment partner [8,20,21], and microbiological data supports transmission or exchange of BV-associated bacteria (henceforth referred to as BV-organisms) during sexual activity [22][23][24][25][26][27]. Notably, BV-organisms are more prevalent in the sub-preputial space (under the foreskin) and distal urethra of male partners of females with BV than without BV [22,26], and recently, the composition of the meatal microbiota was shown to be particularly predictive of incident BV in female partners [24].…”
Section: Background and Rationalementioning
confidence: 99%
“…However, reviews of the early partner treatment trials also highlighted the significant issues that render their findings inconclusive [10,18,19]. Since the publication of these partner-treatment trials, an increasing body of epidemiological data shows women with a regular partner are more likely to experience post-treatment recurrence compared to women with no partner or a new posttreatment partner [8,20,21], and microbiological data supports transmission or exchange of BV-associated bacteria (henceforth referred to as BV-organisms) during sexual activity [22][23][24][25][26][27]. Notably, BV-organisms are more prevalent in the sub-preputial space (under the foreskin) and distal urethra of male partners of females with BV than without BV [22,26], and recently, the composition of the meatal microbiota was shown to be particularly predictive of incident BV in female partners [24].…”
Section: Background and Rationalementioning
confidence: 99%
“…We previously conducted the Strategies to Prevent BV (STOPBV) study, a pilot randomised controlled trial (RCT) investigating the use of the combined (estrogen and progesterone) oral contraceptive pill (COCP) to reduce BV recurrence following antibiotic treatment. While COCP‐exposure did not improve BV‐cure in the pilot RCT, we found that sex with an ongoing RSP and reporting a history of BV were both significantly associated with BV recurrence 16 . If there is a beneficial effect of hormonal contraceptives on the VM in sexually active women, hormonal contraceptives would be a readily available and acceptable intervention for women globally.…”
Section: Introductionmentioning
confidence: 65%
“…This study used prospectively collected specimens derived from the STOPBV study, an open‐label pilot RCT of COCP‐use following first‐line antibiotics to determine the impact on BV recurrence 16 . There was no patient engagement in the study development.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to some studies,9 we found no association between hormonal contraceptive use and persistent BV. A recent randomised controlled pilot study by Vodstrcil et al found no difference in the rate of BV recurrence between women randomised to combined oral contraception or non-hormonal contraception,26 suggesting protective associations may be limited in the context of recurrence.…”
Section: Discussionmentioning
confidence: 99%